The Effect of Government Expenditure on Districts and City in Bali Province, Indonesia - Feny Gusti Wijayanti; Wardatul Fara; Huswatun Hasanah (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
This study aims to determine the effect of tourism, health, infrastructure and the economic expenditures, as well as the Covid-19 pandemic on unemployment and poverty in the Regency/City of Bali Province, Indonesia. The research data used is panel data, consisting of nine regencies and cities in Bali Province 2014-2021. The analysis method used is panel data regression. The results showed that infrastructure expenditure has a significant negative effect on the unemployment rate. Economic expenditure has a significant positive effect on unemployment. During the Covid-19 pandemic, the unemployment rate increased significantly in Bali Province. Meanwhile, infrastructure expenditure and health expenditure have a significant negative effect, and economic expenditure has a significant positive effect on the poverty rate. However, the Covid-19 pandemic did not cause the poverty rate to increase significantly in Bali Province.